(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This work aims to present the results obtained from the development of a didactic sequence that had as its theme the problematization of heartburn in chemistry teaching, because of the Supervised Internship of the Chemistry Degree course at the Instituto Federal Catarinense, with 29 students from 2nd year of high school at a public school in the northern region of Santa Catarina. The collected data were given through the application of a diagnostic questionnaire, participation in the discussion offered during classes and in experimental activities and in the writing of a text. For data analysis, the learning assumptions presented by Moraes, Ramos and Galiazzi (2007) were considered: learning how to reconstruct what is already known; learn how to move in language; speaking, writing and reading as learning tools; resignification of experimentation in chemistry from language. From the discussion of the collected data, it is possible to see evidence of learning at different times: in the interaction, in the questioning of the content, in the moments of demonstrative experiments, configuring that this theme problematized and mobilized various knowledge and knowledge in and for the teaching of chemistry.